Pemberdayaan Siswa dalam Mengenal Bahaya Rokok terhadap Kesehatan dan Upaya Pencegahannya di SMAN 1 Cibadak, Lebak - Ahmad Ahmad; Hadits Lissentiya Armal; Suhartini Suhartini (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Senior High School I Cibadak is one of the schools that does not have a special regulation regarding the application of a No Smoking Area. Meanwhile in school environment, theat smoking behavior of the students is still a problem. Some students are founded smoking in the environment around the school, although it was done secretly. Dedication to community activities aim to increase the knowledge of students and teachers about the dangers of smoking to health and the establishment of a No Smoking Area in SMAN 1 Cibadak, Lebak Regency. The results of dedication community are the first, training of 20 students to availability of promotional media for the prevention of the dangers of smoking, the second making of regulations for SMAN I Cibadak as a Non-Smoking Area (KTR), the third preparation of articles, and the compilation of a pocketbook